Results of a randomized double‐blind study evaluating luvadaxistat in adults with Friedreich ataxia. Issue 6 (20th May 2021) - Wang, Hao; Norton, Jonathan; Xu, Lin; DeMartinis, Nicholas; Sen, Rohini; Shah, Ankit; Farmer, Jennifer; Lynch, David
Abstract: Objectives: Friedreich ataxia (FRDA) is a rare disorder with progressive neurodegeneration and cardiomyopathy. Luvadaxistat (also known as TAK‐831; NBI‐1065844), an inhibitor of the enzyme d ‐amino acid oxidase, has demonstrated beneficial effects in preclinical models relevant to FRDA. This phase 2, randomized, double‐blind, placebo‐controlled, parallel‐arm study evaluated the efficacy and safety of oral luvadaxistat in adults with FRDA. Methods: Adult patients with FRDA were randomized 2:1:2 to placebo, luvadaxistat 75 mg twice daily (BID), or luvadaxistat 300 mg BID for 12 weeks. The primary endpoint changed from baseline at week 12 on the inverse of the time to complete the nine‐hole peg test (9‐HPT −1 ), a performance‐based measure of the function of the upper extremities and manual dexterity. Comparisons between luvadaxistat and placebo were made using a mixed model for repeated measures. Results: Of 67 randomized patients, 63 (94%) completed the study. For the primary endpoint, there was no statistically significant difference in change from baseline on the 9‐HPT −1 (seconds −1 ) at week 12 between placebo (0.00029) and luvadaxistat 75 mg BID (−0.00031) or luvadaxistat 300 mg BID (−0.00059); least squares mean differences versus placebo (standard error) were −0.00054 (0.000746) for the 75 mg dose and −0.00069 (0.000616) for the 300 mg dose. Luvadaxistat was safe and well tolerated; the majority of reported adverse events were mild in intensity. Interpretation: Luvadaxistat was safe and well tolerated in this cohort of adults with FRDA; however, it did not demonstrate efficacy as a treatment for this condition.